Avaliação da participação dos receptores N-metil-D-aspartato (NMDA) e do Fator de Liberação de Corticotropina (CRF) nos efeitos aversivos do óxido nítrico no núcleo intersticial da estria terminal de camundongos - Faria, Matheus Pegoraro (2015)
It has been shown that the bed nucleus of the stria terminalis (BNST) of rats contains nitrergic neurons, which are activated during animal exposure to aversive stimuli. BNST is also populated by glutamatergic and corticotrophin releasing factor (CRFergic) neurons, which in turn, are also activated under stressful situations. Here we investigated the anxiogenic-like effects of intra-BNST injections of a nitric oxide (NO) donor, NOC-9, in mice. The role of CRFergic and glutamatergic systems on defensive behavior induced by NOC-9 was investigated with previous intra-BNST infusion of CP376395 (0, 0.75, 1.50 or 3.00 nmol), a CRF type 1 receptor antagonist (CRF1), or AP-7 (0, 0.05, 0.10 or 0.20 nmol), a NMDA receptor antagonist, respectively. Defensive behavior was assessed immediately and 5 minutes after intra-BNST drug injection, exposing mice to an arena (a neutral situation) and to the elevated plus-maze (EPM; an anxiogenic situation), respectively. Results showed that NOC-9 (all doses) provoked immobility assessed in the arena and increased anxiety in the EPM (e.g., decrease in the percentage of open-arm exploration). Despite failing to produce effects on basal levels of anxiety when injected alone (all doses), pretreatment with CP (3.00 nmol) prevented the anxiogenic-like effect of NOC-9 (75.00 nmol) without changing the immobility behavior. Pretreatment with AP-7 (0.05 nmol) produced similar effects, however, when injected alone 0.20 nmol AP-7 attenuated anxiety-like behavior. These results suggest that the CRF1 and NMDA receptors located within the BNST differentially modulate the aversive effects induced by NO production in this limbic forebrain structure.